Technology Entrepreneurship Project (ENT 600) : Medi-Life (M) Sdn Bhd. / Nik Afiqah N. Ahmad Yani - N. Ahmad Yani, Nik Afiqah (2022)
This study of company analysis is involving one of the medical instrument distributors in Malaysia which is the Medi-Life (M) Sdn Bhd. The company offers various type of products for their customer. Along with the chosen company, the selected product to be analysed in the case study is the wheelchair. By using SWOT analysis, the strengths, weaknesses, opportunities and threats of the products are identified. Several findings and discussion are included in one of the sections in this study. The problems found in this study were stated in this section. After all, together with the recommendation of the solution that should be adopted, an improvement to the new products has been discussed in this section.